Graphene modified high-entropy alloy particle reinforced titanium-based composite material as well as preparation method and application thereof

By modifying high-entropy alloy particles by graphene and using three-dimensional rotation mixing method, the diffusion and solid solution degree of high-entropy alloy elements are regulated, and the problem of poor interface regulation effect of high-entropy alloy reinforced titanium-based composite materials in the prior art is solved, and excellent comprehensive mechanical properties of high strength and high plasticity are achieved.

CN119553137APending Publication Date: 2025-03-04SOUTHEAST UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411789192.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The interface regulation effect of existing high-entropy alloy-enhanced titanium-based composite materials is poor, resulting in large discrete properties and poor repeatability, and often has the problem of strong plasticity mismatch.

Method used

High-entropy alloy particles are modified by graphene, and graphene is uniformly modified on the surface of high-entropy alloy using three-dimensional rotary mixing method, to regulate the diffusion of high-entropy alloy elements and their solid solution degree on the titanium alloy matrix, enhance phase pinning at the particle interface of titanium, and exert the "grain boundary strengthening" effect.

Benefits of technology

It achieves excellent comprehensive mechanical properties of high strength and high plasticity, solves the problems of high discreteness of material properties and poor matching of strong plasticity in the prior art, and improves the repeatability and comprehensive performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119553137A_ABST
    Figure CN119553137A_ABST
Patent Text Reader

Abstract

The invention discloses a graphene modified high-entropy alloy particle reinforced titanium-based composite material and a preparation method and application thereof. According to the composite material, titanium or a titanium alloy serves as a titanium matrix, and graphene is modified on the surface of a high-entropy alloy and serves as a reinforced phase together with the high-entropy alloy to be distributed at the grain boundary of the titanium matrix. In the microstructure of the material, the surface of the high-entropy alloy is modified with graphene, the interface of the high-entropy alloy and a titanium matrix and the solid solution degree of the high-entropy alloy in the titanium alloy matrix are regulated and controlled, and the graphene reacts with the matrix to generate titanium carbide to jointly reinforce the titanium alloy matrix with the high-entropy alloy. According to the preparation method, the graphene is modified on the surfaces of the high-entropy alloy particles by adopting a three-dimensional rotary mixing method, the problem that impurities are easily introduced in a conventional ball milling method is solved, and the graphene-modified high-entropy alloy particle reinforced titanium-based composite material block is obtained through sintering or laser 3D printing forming. The material has high strength and high plasticity, has excellent comprehensive mechanical properties, and can be applied to the fields of aerospace, ships and naval vessels and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of metal-based composite materials, and in particular relates to a graphene-modified high-entropy alloy particle-reinforced titanium-based composite material, a preparation method thereof, and applications thereof. Background Art

[0002] Titanium and its alloys have the characteristics of high strength, low density, heat resistance, corrosion resistance and good formability. Titanium alloys are the main structural materials for aircraft and spacecraft, and are the preferred materials for important components such as aircraft engine fans, compressor wheels and blades. They have also been used in aerospace fields such as tactical missiles, satellites, and launch vehicles. With the further development of the aerospace industry, higher requirements are placed on the comprehensive performance of titanium alloy materials. At the same time, titanium and its alloys also have major problems such as poor wear resistance, low hardness, and strength that needs to be further improved. New ideas and methods are urgently needed to further improve the strength, elastic modulus, service temperature, and wear resistance of titanium alloys, while maintaining good plasticity and machinability, to obtain excellent comprehensive performance and meet the requirements of aerospace materials.

[0003] To improve the mechanical properties of titanium alloys, it is necessary to find new reinforcement materials. The concept of high-entropy alloys: High-entropy alloys are alloy systems with n (5≤n≤13) principal elements, with the atomic percentage of each element not exceeding 35%. Due to their unique elemental composition, arrangement, and interaction potential field, high-entropy alloys exhibit properties that differ significantly from those of traditional alloys. The "four major effects" are the high-entropy effect on thermodynamics, the influence of lattice distortion on structure, the hysteresis diffusion effect on dynamics, and the "cocktail" effect on properties. Compared with traditional alloys, high-entropy alloys have many advantages due to their unique phase structure, including excellent mechanical properties, corrosion resistance, wear resistance, and oxidation resistance. Therefore, high-entropy alloys can be used as excellent reinforcement materials for metal-matrix composites. Research has shown that different high-entropy alloys, such as AlCoCrFeNi, FeCoNiCrMn, and CoCrFeNiMo0.2, have been used as reinforcing phases in metal matrices.

[0004] Graphene nanomaterials are new materials with great development potential after carbon nanotubes. They have similar mechanical properties to carbon nanotubes, but their two-dimensional sheet morphology makes them easier to disperse than carbon nanotubes. In addition, their electrical properties are better than carbon nanotubes and they also have extremely high thermal conductivity.

[0005] The problem faced by current high-entropy alloy reinforced titanium-based composites is that the interface of high-entropy alloy / titanium alloy cannot effectively regulate the degree of diffusion and solid solution of high-entropy alloy into the titanium alloy matrix. It can only be controlled through preparation processes such as temperature, holding time or laser energy of 3D printer. The regulation effect is not good. The performance of each batch is highly discrete and the repeatability is poor. The problem of strength and plasticity mismatch often occurs. How to effectively regulate the interface of high-entropy alloy reinforced titanium-based composites to obtain materials with good repeatability and strong and plastic matching has become an urgent problem to be solved. Summary of the Invention

[0006] Purpose of the Invention: To address the problems existing in the prior art, the present invention proposes a graphene-modified high-entropy alloy particle-reinforced titanium-based composite material. The composite material of the present invention uses a high-entropy alloy as a reinforcing phase uniformly distributed within a titanium alloy matrix. Graphene is modified on the surface of the high-entropy alloy. The thickness and content of the graphene flakes can effectively regulate the diffusion of the high-entropy alloy elements and their degree of solid solution in the titanium alloy matrix. The reinforcing phase is pinned at the titanium particle interfaces, fully utilizing the "grain boundary strengthening" effect to strengthen the beam, thereby achieving higher strength. The high-entropy alloy is an effective grain refiner, so the addition of the high-entropy alloy can refine the grains, thereby achieving better strength and plasticity. Due to the presence of a large titanium matrix region (reinforcement phase-poor region) and the presence of a hard diffusion layer between the high-entropy alloy and the matrix, it can bear strain, resulting in the material having better plasticity. Therefore, the graphene-modified high-entropy alloy particle-reinforced titanium-based composite material has excellent comprehensive mechanical properties combining high strength and high plasticity. The present invention utilizes specific graphene to modify high-entropy alloys, controls the diffusion of high-entropy alloy elements, and also generates a small amount of TiC with the matrix, which not only improves the plasticity but also ensures the strength, effectively solving the problem of large discreteness of mechanical properties and frequent mismatch between strength and plasticity in high-entropy alloy particle-reinforced titanium-based composite materials in the prior art.

[0007] Another object of the present invention is to provide a method for forming a titanium-based composite material reinforced with graphene-modified high-entropy alloy particles. The method comprises modifying the surface of a high-entropy alloy with graphene using a three-dimensional rotational mixing method, mixing the mixture with titanium or titanium alloy powder, and finally sintering or laser 3D printing to obtain the graphene-modified high-entropy alloy particle-reinforced titanium-based composite material.

[0008] Another object of the present invention is to provide graphene-modified high-entropy alloy particle-reinforced titanium-based composite materials for application, which are mainly used in defense and military fields such as aerospace, ships and warships, as spacecraft structural component materials, pressure vessel materials, warehouse bodies, fasteners, structural parts of launch vehicles, satellite structural component materials, component materials of missile warheads, aircraft and aviation engine materials (important components such as fans, compressor wheels and blades), and corrosion-resistant structural materials for ships and warships.

[0009] Technical solution: In order to achieve the above-mentioned purpose, the present invention describes a graphene-modified high-entropy alloy particle-reinforced titanium-based composite material, wherein the graphene-modified high-entropy alloy particle-reinforced titanium-based composite material mainly comprises titanium or titanium alloy as a titanium matrix, and graphene is modified on the surface of the high-entropy alloy and distributed together with the high-entropy alloy as a reinforcing phase at the grain boundaries of the titanium matrix.

[0010] Among them, in the microstructure of the composite material, the graphene is modified on the surface of the high entropy alloy, regulates the interface between the high entropy alloy and the titanium matrix, and reacts with the matrix to generate titanium carbide and the high entropy alloy to jointly strengthen the titanium alloy matrix.

[0011] The graphene is flake graphene with a thickness of 0.1-10 nm and a diameter of 0.1-20 μm; the high entropy alloy is spherical or irregular powder particles with a particle size of 0.01-15 μm, 15-53 μm, 45-105 μm or 45-150 μm; and the titanium matrix is ​​spherical or irregular powder particles with a particle size of 1-15 μm, 15-53 μm, 45-105 μm or 45-150 μm.

[0012] Preferably, the graphene is flake graphene with a thickness of 1-5 nm and a diameter of 5-10 μm; the high entropy alloy is spherical powder particles with a particle size of 15-53 μm; and the titanium matrix is ​​spherical powder particles with a particle size of 15-53 μm.

[0013] Among them, the titanium matrix is ​​pure titanium, or Ti6Al4V or an alloy composed of titanium and other alloying elements such as one or more of Al, Fe, Nb, V, Ta, Zr, Sn, Mo, Cr, W, Ni, B or Si elements; the high entropy alloy is a high entropy alloy composed of any four or more of Fe, Co, Ni, Cr, Mo, Mn, Al, Nb, V, W and Ta.

[0014] Preferably, the high entropy alloy is FeCoNiCrMn.

[0015] The method for preparing the graphene-modified high-entropy alloy particle-reinforced titanium-based composite material of the present invention comprises the following steps:

[0016] (1) Graphene modified high entropy alloy: Graphene powder is mixed with high entropy alloy powder;

[0017] (2) Composite powder mixing: taking the product mixed powder obtained in step (1) and mixing it with pure titanium or titanium alloy powder;

[0018] (3) Drying: The powder mixed in step (2) is vacuum dried and sieved after being completely dried;

[0019] (4) Sintering: The product obtained in step (3) is sintered or laser 3D printed to obtain the graphene-modified high-entropy alloy particle-reinforced titanium-based composite material.

[0020] Wherein, in terms of mass ratio, the addition ratio of the graphene is 0.05%-0.25% of the mass of the high entropy alloy, and the addition ratio of the graphene-modified high entropy alloy is 1.5%-6.0% of the mass of the titanium matrix.

[0021] Preferably, the addition ratio of the graphene is 0.05%-0.1% of the mass of the high entropy alloy, and the addition ratio of the graphene-modified high entropy alloy is 3% of the mass of the titanium matrix.

[0022] Wherein, the method for modifying the surface of high entropy alloy particles with graphene in step (1) is: using a ball mill or a three-dimensional powder mixer at room temperature, placing grinding balls, the ball-to-material ratio is 0.5-3:1, the rotation speed is 50-200r / min, and the mixing time is: 5-32h; the method for mixing the composite powder in step (2) is: using a ball mill or a three-dimensional powder mixer at room temperature, placing grinding balls, the ball-to-material ratio is 0.5-3:1, the rotation speed is 50-200r / min, and the mixing time is: 5-32h.

[0023] Wherein, the sintering in step (4) includes spark plasma sintering or hot pressing sintering, and the conditions of the spark plasma sintering are: pressure of 20-80MPa, temperature of 900-1200℃, holding time of 1-60min, and sintering atmosphere of inert atmosphere or vacuum; the conditions of the hot pressing sintering are: under vacuum or inert atmosphere protection, pressure of 10-50MPa, temperature of 1100-1400℃, heating rate of 10-100℃ / min, and holding time of 10-180min; the conditions of the laser 3D printing in step (4) are: using a laser 3D printer or a selected area electron beam 3D printer to pass high-purity Ar gas inert gas protection after vacuuming, scanning spacing: 50-200μm, scanning speed: 500-3500mm / s, laser power or electron beam power: 100-300W.

[0024] Preferably, the preparation method comprises the following steps:

[0025] (1) Calculation and weighing of original powders: Weigh the corresponding masses of titanium powder, graphene powder and high entropy alloy powder. The addition ratio of graphene is 0.05%-0.25% of the mass of the high entropy alloy powder, and the addition ratio of graphene-modified high entropy alloy is 1.5%-6% of the mass of the titanium matrix.

[0026] (2) Graphene modified high entropy alloy: Take the corresponding mass fraction of graphene powder and high entropy alloy powder in step (1), put them into a powder mixing bottle, add stainless steel grinding balls, and the ball-to-material ratio is 0.5-3:1. Put them into a three-dimensional powder mixer for mixing at a speed of 50-200 r / min and a mixing time of 5-32 h to obtain high entropy alloy powder with surface modified graphene.

[0027] (3) Composite powder mixing: Take the corresponding mass fractions of high entropy alloy powder and titanium powder from step (2), place them in a powder mixing bottle, add stainless steel grinding balls, and mix them in a three-dimensional powder mixer at a ball-to-powder ratio of 0.5-3:1. The mixture is mixed at a speed of 50-200 r / min and a mixing time of 5-32 h.

[0028] (4) Place the mixed powder in a vacuum drying oven and vacuum dry it for 1-10 hours at a drying temperature of 40-120°C. After it is completely dried, sieve it with a 100-400 mesh sieve.

[0029] (5) Sintering: Determine the dimensional parameters of the sintered product and, after calculation, weigh a certain mass of the product from step (4). Finally, spark plasma sintering or other molding methods can be used to produce the product.

[0030] a. Spark plasma sintering molding method: Pour the powder of (4) into a graphite mold, assemble the upper and lower pressure heads, and place it in a spark plasma sintering furnace for sintering molding. Under vacuum or high-purity argon protection, the pressure is 20-80 MPa, the temperature is 900-1200°C, the temperature is measured by thermocouple or infrared temperature measurement, the heating rate is 20-300°C / min, and the holding time at the highest sintering temperature is 1-60 minutes. The furnace is naturally cooled and the product is demolded.

[0031] Alternatively, hot pressing sintering can be used:

[0032] b. Hot Pressing and Sintering Method: Pour the powder of (4) into a graphite mold, assemble the upper and lower pressing heads, and place the mold in a hot press sintering furnace for sintering. Under vacuum or inert atmosphere, the pressure is 10-50 MPa, the temperature is 1100-1400°C, the heating rate is 10-100°C / min, and the holding time at the highest sintering temperature is 10-180 minutes. Cool naturally in the furnace and demold to obtain the product.

[0033] Alternatively, laser 3D printing can be used:

[0034] c. Laser 3D printing method: put the powder of (4) into the powder bin of the laser 3D printing equipment, evacuate the powder bin and introduce Ar gas for inert gas protection, scan spacing: 50-200 μm, scan speed: 500-3500 mm / s, laser power or electron beam power: 100-300 W.

[0035] The graphene-modified high-entropy alloy particle-reinforced titanium-based composite material of the present invention is used as a material for aerospace or ship components.

[0036] Among them, the aerospace or ship component materials include spacecraft structural component materials, launch vehicle pressure vessel materials, satellite structural component materials, missile body component materials, aircraft and aviation engine material structural materials or ship corrosion-resistant structural materials, etc.

[0037] The present invention modifies graphene on a high-entropy alloy particle-reinforced titanium-based composite material. Graphene is modified on the surface of a high-entropy alloy powder so that the graphene is uniformly modified on the surface of the titanium-based particles. The graphene-modified high-entropy alloy powder is mixed with a titanium alloy powder and finally sintered to form a composite material. Titanium carbide particles are generated in situ between the graphene and the titanium matrix at the interface, forming a titanium-based composite material synergistically reinforced by the high-entropy alloy and titanium carbide. Currently, there is no technology for modifying graphene on the surface of a high-entropy alloy powder. Traditional modification techniques mainly involve ball milling the matrix and the modified powder. This relies on long-term collisions between the grinding balls to allow the graphene to adhere to the particle surface. This method is prone to introducing impurities and easily destroying the morphology and structure of the matrix and graphene, thereby affecting the performance of the composite material after sintering. In the present invention, a three-dimensional rotating mixer is used to modify the graphene on the surface of the high-entropy alloy particles without destroying the original structure and morphology of the high-entropy alloy particles and the graphene, achieving an excellent dispersion modification effect. In the subsequent spark plasma rapid sintering, the graphene can be directly densified and formed, thereby simplifying the preparation process and shortening the production cycle.

[0038] The graphene-modified high-entropy alloy particle-reinforced titanium-based composite prepared by the present invention exhibits numerous advantages, including excellent mechanical properties, corrosion resistance, wear resistance, and oxidation resistance, due to its unique phase structure. Therefore, high-entropy alloys can be used as excellent reinforcement materials for metal-based composites. Research has shown that various high-entropy alloys can be used as reinforcement phases in metal matrices. Graphene exhibits low density, large specific surface area, high strength, and high modulus. The in-situ generated titanium carbide bonds tightly with the matrix, resulting in a cleaner interface and excellent mechanical properties. Graphene-modified high-entropy alloy particle reinforcement can effectively enhance the strength of the composite while maintaining a certain degree of plasticity. The reinforcement phase is pinned to the titanium particle interfaces, fully utilizing the "grain boundary strengthening" effect to reinforce the beam, resulting in higher strength. High-entropy alloys are effective grain refiners, so their addition can refine the grains, resulting in improved strength and plasticity. The presence of a large titanium matrix region (a region poor in reinforcement phase) and a hard diffusion layer between the high-entropy alloy and the matrix acts to bear strain, resulting in the material's excellent plasticity. Therefore, graphene modification has excellent comprehensive properties in high-entropy alloy particle-reinforced titanium-based composites, which broadens the application of titanium alloys in the aerospace field.

[0039] The present invention utilizes high-entropy alloy particles to reinforce titanium-based composite materials, forming an element diffusion zone between the particles and the matrix. By modifying the surface of the high-entropy particles with graphene, the diffusion rate and degree of solid solution of the high-entropy alloy elements in the matrix are controlled, thereby regulating the mechanical properties of the composite material. This invention is the first to utilize graphene to modify high-entropy particles and serve as a reinforcing phase. The graphite flakes partially adhere to or coat the surface of the high-entropy alloy and, together with the high entropy, serve as a reinforcing phase distributed at the grain boundaries of the titanium matrix. Compared to unreinforced titanium alloys, within a certain range of available plasticity, the hardness and strength can be significantly improved. Compared to titanium-based composite materials reinforced with high-entropy alloys, not only can the plasticity be improved, but the strength can also be significantly improved.

[0040] In addition, the amount and thickness of graphene added in the present invention have a significant impact on the mechanical properties of the synthesized graphene modified in the high entropy alloy particle reinforced titanium-based composite material. Compared with the high entropy alloy particle reinforced titanium-based composite material without graphene, the material strength and plasticity of the graphene added in the present invention are reduced when the amount of graphene added is above or below 0.1%. The optimized graphene reinforcement base content is 0.10wt%, which can not only significantly improve the strength, but also keep the plasticity within the preferred usable range. At the same time, the average thickness of the graphene in the present invention is optimal at 1-5nm, but the average thickness of the graphene is above 10nm, which is a multi-layer graphene sheet, and the multi-layer graphene sheets slide; or the graphene below 1nm is a single layer or double layer graphene, which is expensive and reacts completely with the metal matrix, forming all carbides, losing the excellent performance of graphene, not only failing to improve the strength of the composite material, but also significantly reducing the mechanical properties such as plasticity.

[0041] Beneficial effects: Compared with the prior art, the present invention has the following advantages:

[0042] The present invention discloses a graphene-modified high-entropy alloy particle-reinforced titanium-based composite material. Graphene is modified on the surface of a high-entropy alloy powder so that the graphene is uniformly modified on the surface of the titanium-based particles. The graphene-modified high-entropy alloy powder is mixed with the titanium alloy powder, and finally sintered or laser 3D printed to obtain a composite material. Titanium carbide particles are generated in situ between the graphene and the titanium matrix at the interface, forming a titanium-based composite material synergistically reinforced by the high-entropy alloy and titanium carbide. The present invention prepares a graphene-modified high-entropy alloy particle-reinforced titanium-based composite material having excellent comprehensive mechanical properties such as high strength and high plasticity.

[0043] At the same time, compared with the existing ball milling powder mixing technology, the method of the present invention uses a three-dimensional rotational mixing method to well modify the surface of high-entropy alloy particles with graphene, overcoming the difficulties of the ball milling method in easily introducing impurities and making it difficult to achieve uniform modification of high-entropy alloy powder with graphene nanoparticles. After sintering and molding, a graphene-modified high-entropy alloy particle-reinforced titanium-based composite material is obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 X-ray diffractometer patterns of high entropy alloy particles reinforced titanium matrix composites and Ti6Al4V modified with different addition contents of graphene;

[0045] Figure 2 The microhardness trend diagram of different positions of the titanium matrix composite network reinforced with high entropy alloy particles modified with different addition contents of graphene (compared with unreinforced titanium alloy);

[0046] Figure 3 The tensile curves of high-entropy alloy particles reinforced titanium matrix composites and Ti6Al4V with different addition contents of graphene (compared with unreinforced titanium alloy and high-entropy alloy particles reinforced titanium matrix composites);

[0047] Figure 4 Images of the original powder (A, B), metallographic microscope image (C), and scanning electron microscope morphology image (D) of titanium-based composites modified with high-entropy alloy particles with different addition contents of graphene;

[0048] Figure 5 Scanning electron microscope morphology of the tensile cross-section of titanium matrix composite products reinforced with high entropy alloy particles modified with different addition contents of graphene;

[0049] Figure 6 Tensile curves of titanium-based composites reinforced with graphene-modified high-entropy alloy particles and Ti6Al4V prepared by laser 3D printing (compared with unreinforced titanium alloy). DETAILED DESCRIPTION

[0050] The present invention will be further described below with reference to the accompanying drawings and examples.

[0051] Unless otherwise specified, the materials and reagents used in the following examples are all commercially available. Experimental methods without specific conditions specified in the examples are generally performed under conventional conditions or the conditions recommended by the manufacturer.

[0052] Among them, FeCoNiCrMn high entropy alloy powder of 0.01-15 μm or 15-53 μm or 45-105 μm or 45-150 μm, Ti powder of 1-15 μm or 15-53 μm or 45-105 μm or 45-150 μm or TC4 powder are all commercially available.

[0053] Graphene sheets with a thickness of 1-5 nm and a diameter of 5-10 μm, graphene sheets with a thickness of 5-10 nm and a diameter of 10-20 μm, and graphene sheets with a thickness of 8-10 nm and a diameter of 8-10 μm are all commercially available.

[0054] Example 1

[0055] Graphene-modified high-entropy alloy particle-reinforced titanium-based composites are produced by spark plasma sintering technology. Graphene powder, spherical FeCoNiCrMn high-entropy alloy powder and spherical Ti6Al4V (TC4) powder are used as raw materials. The graphene sheets have a thickness of 1-5nm and a diameter of 5-10μm. The particle size of the FeCoNiCrMn high-entropy alloy powder is 15-53μm, and the particle size of the TC4 powder is 15-53μm.

[0056] The specific steps are as follows:

[0057] (1) Weigh 50 g of FeCoNiCrMn powder and add it to a mixing bottle with graphene powder at concentrations of 0.05, 0.10, 0.15, 0.20, and 0.25 wt.% of the high-entropy alloy mass, respectively. Stainless steel grinding balls are then added to the bottle at a 1:1 ratio of mass to the mixed powder. The mixing bottle is placed in a three-dimensional mixer with the following parameters: speed: 70 rpm, mixing time: 16 h.

[0058] (2) Weigh 100 g of TC4 powder and add 1.5, 3.0, 4.5, and 6.0 wt.% of graphene-modified high-entropy alloy powder to a mixing bottle. Stainless steel grinding balls are then added to the bottle at a 1:1 ratio of mass to the mixed powder. The mixing bottle is placed in a three-dimensional mixer with the following parameters: speed: 70 rpm, mixing time: 16 h.

[0059] (3) The mixed powder of graphene-modified high-entropy alloy powder and TC4 was placed in a vacuum drying oven at 60°C for 3 h. After being completely dried, the mixture was sieved with an 80-mesh sieve.

[0060] (4) Take an appropriate amount of the powder from (3) and pour it into a 30 mm diameter graphite mold. Assemble the upper and lower pressure heads and place it in a spark plasma sintering furnace. The SPS sintering parameters are: Ar atmosphere, infrared temperature measurement, and a heating rate of 50°C / min. Raise the temperature to 1000°C, pressure 60 MPa, and sinter at 1000°C for 10 minutes to make the material dense and then cool the furnace to room temperature. The relative density of the sintered product is measured by the Archimedean method, and the calculated density is as high as 99.8%.

[0061] The control group used TC4 finished products and high-entropy alloy particle-reinforced titanium-based composite materials without adding graphene. The TC4 finished products were processed by TC4 powder according to the spark plasma sintering method of the above step (4); the high-entropy alloy particle-reinforced titanium-based composite materials without adding graphene were processed according to the above method without adding graphene, and the other steps were the same as steps (2)-(4).

[0062] Performance testing and organizational structure analysis: The samples were analyzed by X-ray diffractometer for phase analysis, microhardness was measured by microhardness tester, compression test was carried out by microcomputer-controlled electronic universal tester, and finally the microstructure of graphene-reinforced titanium-based composite materials was analyzed by transmission electron microscopy, and the fracture morphology was observed and analyzed by scanning electron microscopy.

[0063] in, Figure 1 XRD patterns of titanium-based composite materials reinforced with graphene-modified high-entropy alloy particles and TC4 with different contents. The addition ratio of graphene-modified high-entropy alloy is 3wt% of the titanium matrix. Due to the low content of added graphene and high-entropy alloy, they could not be measured.

[0064] Figure 2 The hardness of titanium-based composites was enhanced by adding different amounts of graphene-modified high-entropy alloy particles, with the addition ratio of the graphene-modified high-entropy alloy being 3wt% of the titanium matrix. Compared with the unreinforced titanium alloy, the graphene-modified high-entropy alloy particles significantly increased the hardness.

[0065] Figure 3The stress-strain trend diagram for the tensile strength of the prepared composite material, in which the addition ratio of graphene-modified high-entropy alloy is 3wt% of the titanium matrix, shows that the graphene-modified high-entropy alloy particles significantly improve the strength compared to the unreinforced titanium alloy (TC4). Compared with the titanium-based composite material reinforced with high-entropy alloy particles without graphene (TC4-3wt% HEA(0GR)), the materials with graphene additions above 0.1% (e.g., 0.15%) increase strength but decrease plasticity. The materials with graphene additions of 0.1% or less (e.g., 0.05%) not only increase strength but also improve plasticity to a certain extent. The optimized graphene reinforcement matrix content is 0.10wt%, which not only significantly improves strength but also maintains high plasticity under high performance conditions. In other cases, the addition of graphene cannot simultaneously maintain high levels of strength and plasticity. This also shows that titanium-based composite materials with different strength and plasticity can be prepared by adjusting the addition of different graphene contents according to the mechanical strength requirements of different applications.

[0066] At the same time, the graphene sheets in this embodiment are replaced with graphene sheets with an average thickness of less than 1 nm or greater than 10 nm, and the graphene modification amount (0.1 wt%) and the graphene-modified high-entropy alloy addition amount (3 wt%) are carried out according to the above-mentioned optimal addition ratio. Compared with the high-entropy alloy particle-reinforced titanium-based composite material without adding graphene, its strength and plasticity will be reduced.

[0067] Figure 4 Scanning electron micrographs (A, B) of a pristine high-entropy alloy (HEA) powder modified with 0.10 wt% graphene, and metallographic micrographs (C) and scanning electron micrographs (D) of titanium-based composites modified with 0.10 wt% and 3 wt% graphene-modified HEA powders, show that graphene can be added to the HEA surface using the three-dimensional rotational mixing method. Furthermore, HEA particles are distributed at the interface of the titanium-based composite, where graphene reacts with the matrix to form titanium carbide, which is distributed in the matrix and contains residual graphene on the HEA particles.

[0068] Figure 5 The scanning electron microscope morphology photos of the tensile fracture surface of the titanium-based composite material with 0.10wt% graphene and 3wt% graphene modified high entropy alloy powder can be seen. It can be seen that there are tear ridges and a large number of dimples in the titanium matrix, indicating that ductile fracture occurred in the matrix, while cracks appeared at the high entropy particles, indicating that brittle fracture occurred at the high entropy alloy, and mixed fracture occurred in the entire titanium-based composite material.

[0069] Example 2

[0070] Spark plasma sintering is used to produce graphene-modified high-entropy alloy particle-reinforced titanium-based composites. Graphene powder, spherical FeCoNiCrMn high-entropy alloy powder, and spherical Ti6Al4V (TC4) powder are used as raw materials. The graphene sheets have a thickness of 5-10 nm and a diameter of 10-20 μm. The particle size of the FeCoNiCrMn high-entropy alloy powder is 15-53 μm, and the particle size of the TC4 powder is 15-53 μm.

[0071] The specific steps are as follows:

[0072] (1) Weigh 50 g of FeCoNiCrMn powder and add it to a mixing bottle with graphene powder at concentrations of 0.05, 0.10, 0.15, 0.20, and 0.25 wt.% of the total mass of the high-entropy alloy. Stainless steel grinding balls are then added to the bottle at a 1:1 ratio of mass to the mixed powder. The mixing bottle is placed in a three-dimensional mixer with the following parameters: speed: 70 rpm, mixing time: 16 h.

[0073] (2) Weigh 100 g of TC4 powder and add 1.5, 3.0, 4.5, and 6.0 wt.% of graphene-modified high-entropy alloy powder to a mixing bottle. Stainless steel grinding balls are then added to the bottle at a 1:1 ratio of mass to the mixed powder. The mixing bottle is placed in a three-dimensional mixer with the following parameters: speed: 70 rpm, mixing time: 16 h.

[0074] (3) The mixed powder of graphene-modified high-entropy alloy powder and TC4 was placed in a vacuum drying oven at 60°C for 3 h. After being completely dried, the mixture was sieved with an 80-mesh sieve.

[0075] (4) Take an appropriate amount of the powder from (3) and pour it into a graphite mold with a diameter of 50 mm. Install the upper and lower pressure heads and place it in a spark plasma sintering furnace. The spark plasma sintering parameters are: vacuum protection, infrared temperature measurement, and a heating rate of 100°C / min. Heat to 950°C, pressure 50 MPa, and sinter for 10 minutes to make the material dense and compact. Then cool the furnace to room temperature. The relative density of the sintered product is measured by the Archimedean method, and the calculated density is as high as 99.7%.

[0076] Performance testing and organizational structure analysis: The samples were analyzed by X-ray diffractometer for phase analysis, microhardness was measured by microhardness tester, compression test was carried out by microcomputer-controlled electronic universal tester, and finally the microstructure of graphene-reinforced titanium-based composite materials was analyzed by transmission electron microscopy, and the fracture morphology was observed and analyzed by scanning electron microscopy.

[0077] Example 3

[0078] Graphene-modified high-entropy alloy particle-reinforced titanium-based composites are produced by vacuum hot pressing and sintering. Graphene powder, spherical FeCoNiCrMn high-entropy alloy powder, and spherical Ti6Al4V (TC4) powder are used as raw materials. The graphene sheets have a thickness of 8-10 nm and a diameter of 8-10 μm. The particle size of the FeCoNiCrMn high-entropy alloy powder is 0.01-15 μm, and the particle size of the TC4 powder is 45-150 μm.

[0079] The specific steps are as follows:

[0080] (1) Weigh 50 g of FeCoNiCrMn powder and add it to a mixing bottle with graphene powder at concentrations of 0.05, 0.10, 0.15, 0.20, and 0.25 wt.% of the high-entropy alloy mass, respectively. Stainless steel grinding balls were then added to the bottle at a 1:1 ratio of mass to the mixed powder. The mixing bottle was placed in a three-dimensional mixer with the following parameters: speed: 70 rpm, mixing time: 32 h.

[0081] (2) Weigh 100 g of TC4 powder and add 1.5, 3.0, 4.5, and 6.0 wt.% of graphene-modified high-entropy alloy powder to a mixing bottle. Stainless steel grinding balls are then added to the bottle at a 1:1 ratio of mass to the mixed powder. The mixing bottle is placed in a three-dimensional mixer with the following parameters: speed: 70 rpm, mixing time: 32 h.

[0082] (3) The mixed powder of graphene-modified high-entropy alloy powder and TC4 was placed in a vacuum drying oven at 60°C for 3 h. After being completely dried, the mixture was sieved with an 80-mesh sieve.

[0083] (4) Take an appropriate amount of the powder from (3) and pour it into a graphite mold with a diameter of 50 mm. Install the upper and lower pressure heads and place it in a vacuum hot pressing sintering furnace. The sintering parameters are: vacuum protection, infrared temperature measurement, and a heating rate of 10°C / min. Heat to 1250°C, pressure 30 MPa, and sinter for 60 minutes to make the material dense and compact. Then cool the furnace to room temperature. The relative density of the sintered product is measured by the Archimedean method, and the calculated density is as high as 99.8%.

[0084] Performance testing and organizational structure analysis: The samples were analyzed by X-ray diffractometer for phase analysis, microhardness was measured by microhardness tester, compression test was carried out by microcomputer-controlled electronic universal tester, and finally the microstructure of graphene-reinforced titanium-based composite materials was analyzed by transmission electron microscopy, and the fracture morphology was observed and analyzed by scanning electron microscopy.

[0085] Example 4

[0086] 3D printing technology is used to produce graphene-modified high-entropy alloy particle-reinforced titanium-based composites, using graphene powder, spherical FeCoNiCrMn high-entropy alloy powder and spherical Ti6Al4V (TC4) powder as raw materials. The graphene sheets have a thickness of 1-5nm and a diameter of 5-10μm. The particle size of the FeCoNiCrMn high-entropy alloy powder is 15-53μm, and the particle size of the TC4 powder is 15-53μm.

[0087] The specific steps are as follows:

[0088] (1) Weigh 50 g of FeCoNiCrMn powder and add it to a mixing bottle with graphene powder at concentrations of 0.05, 0.10, 0.15, 0.20, and 0.25 wt.% of the high-entropy alloy mass, respectively. Stainless steel grinding balls were then added to the bottle at a 1:1 ratio of mass to the mixed powder. The mixing bottle was placed in a three-dimensional mixer with the following parameters: speed: 70 rpm, mixing time: 32 h.

[0089] (2) Weigh 500 g of TC4 powder and add 1.5, 3.0, 4.5, and 6.0 wt.% of graphene-modified high-entropy alloy powder to a mixing bottle. Stainless steel grinding balls are then added to the bottle at a 1:1 ratio of mass to the mixed powder. The mixing bottle is placed in a three-dimensional mixer with the following parameters: speed: 70 rpm, mixing time: 32 h.

[0090] (3) The mixed powder of graphene-modified high-entropy alloy powder and TC4 was placed in a vacuum drying oven at 60°C for 3 h. After being completely dried, the mixture was sieved with an 80-mesh sieve.

[0091] (4) The powder of (3) was poured into the printing powder bin of the M2150T 3D printer manufactured by Nanjing Chenglian Laser Technology Co., Ltd., and high-purity Ar gas was introduced after vacuuming. The 3D printing parameters were: scanning spacing: 50 μm, scanning speed: 1200 mm / s, and laser power: 150 W. Figure 6 This is a diagram of the mechanical properties after laser 3D printing. It can be seen that the strength and plasticity of the titanium-based composite material prepared with 0.10wt% graphene and 3wt% graphene-modified high-entropy alloy powder are both higher than those of the TC4 finished product prepared under these preparation conditions and the high-entropy alloy particle-reinforced titanium-based composite material without graphene.

[0092] Performance testing and organizational structure analysis: The samples were analyzed by X-ray diffractometer for phase analysis, microhardness was measured by microhardness tester, compression test was carried out by microcomputer-controlled electronic universal tester, and finally the microstructure of graphene-reinforced titanium-based composite materials was analyzed by transmission electron microscopy, and the fracture morphology was observed and analyzed by scanning electron microscopy.

Claims

1. A graphene-modified high-entropy alloy particle-reinforced titanium-based composite material, characterized in that: The graphene-modified high-entropy alloy particle-reinforced titanium-based composite material mainly comprises titanium or titanium alloy as a titanium matrix, and graphene is modified on the surface of the high-entropy alloy and distributed together with the high-entropy alloy as a reinforcement phase at the grain boundary of the titanium matrix.

2. The graphene-modified high-entropy alloy particle-reinforced titanium-based composite material according to claim 1, characterized in that: The graphene is modified on the surface of the high entropy alloy, regulates the interface between the high entropy alloy and the titanium matrix and the degree of solid solution of the high entropy alloy in the titanium alloy matrix, and reacts with the matrix to generate titanium carbide and the high entropy alloy to jointly strengthen the titanium alloy matrix.

3. The graphene-modified high-entropy alloy particle-reinforced titanium-based composite material according to claim 1, characterized in that: The graphene is flaky graphene with a thickness of 0.1-10 nm and a diameter of 0.1-20 μm; the high entropy alloy is spherical or irregular powder particles with a particle size of 0.01-15 μm, 15-53 μm, 45-105 μm or 45-150 μm; the titanium matrix is ​​spherical or irregular powder particles with a particle size of 1-15 μm, 15-53 μm, 45-105 μm or 45-150 μm.

4. The graphene-modified high-entropy alloy particle-reinforced titanium-based composite material according to claim 1, characterized in that: The titanium matrix is ​​preferably pure titanium, or Ti6Al4V or an alloy of titanium and other alloying elements such as one or more of Al, Fe, Nb, V, Ta, Zr, Sn, Mo, Cr, W, Ni, B or Si elements; the high entropy alloy is a high entropy alloy composed of any three or more of Fe, Co, Ni, Cr, Mo, Mn, Al, Nb, V, W and Ta.

5. A method for preparing the graphene-modified high-entropy alloy particle-reinforced titanium-based composite material according to claim 1, characterized in that: The following steps are involved: (1) Graphene modified high entropy alloy: graphene powder and high entropy alloy powder are mixed; (2) Composite powder mixing: taking the mixed powder obtained in step (1), and mixing it with pure titanium or titanium alloy powder; (3) Drying: The powder mixed in step (2) is vacuum dried and sieved after being completely dried; (4) Sintering: The product obtained in step (3) is sintered or laser 3D printed to obtain the graphene-modified high-entropy alloy particle-reinforced titanium-based composite material.

6. The method for preparing the graphene-modified high-entropy alloy particle-reinforced titanium-based composite material according to claim 5, characterized in that: In terms of mass ratio, the addition ratio of the graphene is 0.05%-0.25% of the high entropy alloy, and the addition ratio of the graphene-modified high entropy alloy is 1.5%-6.0% of the mass of the titanium matrix.

7. The method for preparing the graphene-modified high-entropy alloy particle-reinforced titanium-based composite material according to claim 5, characterized in that: In step (1), the method for modifying the surface of high entropy alloy particles with graphene is as follows: a ball mill or a three-dimensional powder mixer is used at room temperature, grinding balls are placed in the mixture, the ball-to-material ratio is 0.5-3:1, the rotation speed is 50-200 r / min, and the mixing time is 5-32 h; and the method for mixing composite powders in step (2) is as follows: a ball mill or a three-dimensional powder mixer is used at room temperature, grinding balls are placed in the mixture, the ball-to-material ratio is 0.5-3:1, the rotation speed is 50-200 r / min, and the mixing time is 5-32 h.

8. The method for preparing the graphene-modified high-entropy alloy particle-reinforced titanium-based composite material according to claim 5, characterized in that: The sintering in step (4) includes spark plasma sintering or hot pressing sintering. The conditions of the spark plasma sintering are: pressure of 20-80MPa, temperature of 900-1200°C, holding time of 1-60min, and sintering atmosphere of inert atmosphere or vacuum; the conditions of the hot pressing sintering are: under vacuum or inert atmosphere protection, pressure of 10-50MPa, temperature of 1100-1400°C, heating rate of 10-100°C / min, and holding time of 10-180min; the conditions of the laser 3D printing in step (4) are: using a laser 3D printer to pass high-purity Ar gas inert gas protection after vacuuming, scanning spacing: 50-200μm, scanning speed: 500-3500mm / s, laser power or electron beam power: 100-300W.

9. Use of the graphene-modified high-entropy alloy particle-reinforced titanium-based composite material according to claim 1 as a material for aerospace or ship components.

10. The use according to claim 9, characterized in that: The aerospace or ship component materials include spacecraft structural component materials, launch vehicle pressure vessel materials, satellite structural parts materials, missile body component materials, aircraft and aeroengine material structural materials or ship corrosion-resistant structural materials.

Citation Information

Cited By

  • Reduced graphene oxide / high-entropy alloy reinforced aluminum alloy bar and preparation method thereof

    CN120174228A

  • Reduced graphene oxide / high entropy alloy reinforced aluminum alloy rods and their preparation methods

    CN120174228B